Humanizing Big Data: Recognizing the Human Aspect of Big Data - Helzlsouer, Kathy; Meerzaman, Daoud; Taplin, Stephen; Dunn, Barbara K. (Frontiers in Oncology, 2020)
Genetic testing for germline variants for the purpose of clarifying inherited risk for diseases such as cancer or for ancestry has become widely accepted in the non-research setting. A number of advanced technologies such as microarrays and, more recently, next-generation sequencing, enable testing of thousands of genes and variants simultaneously. The choice of technology depends on the clinical presentation or the non-medical question. In the clinical setting, these tests provide assessment of variants known to confer propensity to disease, e.g. cancer. While much of the knowledge about specific inherited variants that increase cancer risk derives from associations based on analysis of “big data” accumulated from thousands of individuals tested in a wide variety of settings, applying that information back to an individual and their situation has been challenging. Ideally, pre-test genetic counseling, particularly when the purpose relates to disease risk, is carried out to assess the value of testing and what test to apply to a given individual based on family history and assorted other individual characteristics. It is critical to remember, especially in the current climate of intensive commercial promotion of genetic testing, notably in the direct-to-consumer setting, the particular needs of the individual person whose medical or other purpose brought them to the attention of genetic testing services and to provide them with the information they require for making decisions to test, including interpreting appropriately the test results and ensuring adequate management given results of the tests. In this paper, our goal is to bring the sophisticated technology of genetic/genomic testing and the resulting generation of “big data” down to the human level, where the impact on individual lives can be addressed and understood.